SIMULATORS IN THE TRAINING OF FUTURE SHIP NAVIGATORS - Popova G. (Kherson State University, 2018)
The development of technologies, informatization of navigation requires changes in the formation of professional competencies of future marine specialists. The article is devoted to the use of virtual reality simulators in higher education institutions in the preparation of marine specialists, the practical orientation of the educational process, taking into account the advanced international experience of navigation in the field of simulation and compliance with modern innovative technologies. The article is devoted to the search of new methodological approaches to the training of future ship navigators using modern technologies of virtual reality, known as simulation training. The role and place of virtual reality simulation technologie, taking into account the competence approach, results of application of simulation technologies of virtual reality in the system of professional training of future ship navigators is analyzed. On the example of creating a simulation center "Virtual-Real Ship" in the Kherson State Maritime Academy a system of professional competencies of future navigators formation has been demonstrated. It is shown that the use of virtual reality simulation technologies allows us to recreate the close connection of the educational process with the practice, to simulate real professional situations, to adapt the learning process to specific professional tasks, to objectively evaluate the level of professional training, to increase the level of professional competencies and personal qualities formation future ship navigators, to expose the practical skills of navigation to a qualitatively new level without threatening the life and health of people. Navigation simulators to a large extent ensure implementation of psychological and didactic requirements for the process of forming the professional competence of future ship navigators.